Vibrações do corpo-escola: as fabulações das crianças em redes de criação coletiva - Zouain, Ana Cláudia Santiago (2025)
This thesis is an invitation to embark on the vibrations of the school-body through the nomadic wanderings of children and teachers. In this movement, we evoke shared experiments in daily encounters as collective creations. Therefore, we defend the thesis that children's fables vibrate thought, in the understanding of school as a place of multiple lives, in collective networks of affection. Our bet unfolds in the tension of other images of childhood, curriculum, learning and teaching, by affirming an early childhood education of the sensitive, where representation and cognitive practices are necessary, however, not sufficient to compose the educational process, which is strengthened in the coalescence of the plane of immanence and the plane of consistency, driving divergent, predicted and unforeseen, but not dichotomous, constantly occurring flows. The research was carried out in a municipal early childhood education center in Vitória, Espírito Santo. It brings, as a theoretical-methodological contribution, sentimental cartography with conversation networks, dialoguing with the Philosophy of Difference. Thus, it makes use of concepts developed by Deleuze, Guattari, Bergson, Lapoujade, Rolnik and other thinkers. It understands that, with collective experiments, networks of multiplicities intensify in the composition of a school as a place of life in expansive communality